PEMANFAATAN ABU KULIT KAKAO UNTUK PEMBUATAN BATU BATA - -, Mulyazmi; Praputri, Erti; -, Zulfiandriana; Wahyuni, Widya (Universitas Andalas, 2015)
Brick is one of building materials derived from clay. The manufacturing process is with or without the use of substances mixing with the process of combustion at high temperatures. One of the mixing substances is derived from the rind cacao ash and its function is as an adhesive on the bricks.The purpose of this research is to understand the characteristics of brick as effect of cocoa rind as the value of compressive strength, porosity, water absorption and weight of a brick. The main materials of brick production are clays and trass ground which are mixed homogeneous with ratio 1 : 2 by varying cocoa rind ash additional by 5%, 10%, and 15%. The result is the compressive strength of the bricks using rind cocoa ash is 392.2 kg/cm3 higher value than traditional brick is 56.1 kg/cm3.